Cardiac pacing: diagnostic and therapeutic tools - Cardiac pacing: diagnostic and therapeutic tools; Luderitz B. (editor) (Berlin Springer-Verlag, 1976)
The Papers Were Presented at the International Symposion on "Diagnostic and Therapeutical Tools of Cardiac Pacing" Held at Munich on November 7 and 8, 1975.